1999
DOI: 10.1002/1529-0131(199904)42:3<421::aid-anr5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic polyangiitis: Clinical and laboratory findings in eighty-five patients

Abstract: This study demonstrated that MPA is a multisystemic disease in which renal symptoms are frequent, but the disease is also associated with general symptoms, arthritis, mononeuritis multiplex, and other manifestations that are also seen in various vasculitides. The rarity of abnormal angiogram findings and the high frequency of pANCA are characteristic of MPA. In most cases, the outcome is comparable with those of other systemic vasculitides, but relapses are frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
359
5
49

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 755 publications
(436 citation statements)
references
References 16 publications
15
359
5
49
Order By: Relevance
“…In patients with MPA, a wide range of organ systems can be affected (1)(2)(3). The lung is one of the major organs involved, and recent studies demonstrated that pulmonary involvement is associated with unfavorable outcomes (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with MPA, a wide range of organ systems can be affected (1)(2)(3). The lung is one of the major organs involved, and recent studies demonstrated that pulmonary involvement is associated with unfavorable outcomes (4,5).…”
mentioning
confidence: 99%
“…The lung is one of the major organs involved, and recent studies demonstrated that pulmonary involvement is associated with unfavorable outcomes (4,5). Diffuse alveolar hemorrhage (DAH) is a well-described pulmonary manifestation of small vessel vasculitis (3,6). However, interstitial lung disease (ILD) was recently recognized as a major pulmonary manifestation in patients with MPA (7,8), although its pathogenesis remains largely unknown.…”
mentioning
confidence: 99%
“…According to a previous report, the frequency of respiratory involvement in renal vasculitis including MPA and GPA is similar between UK and Japan, whereas the frequency of neurological involvement is significantly lower in Japan [1]. Among neurologic manifestations in patients with MPA, intracerebral hemorrhage has rarely been reported, but it leads to poor outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of onset of MPO-ANCA-associated GN in Japan is reported to be 66.6 years old [3] and the annual incidence of ANCA-associated vasculitis is 22.6 per million adults [4]. Since severe extra-renal complications such as pulmonary hemorrhage (25-55 %), interstitial pneumonia (10 %), and gastro-intestinal bleeding (10 %) are observed [5][6][7], early diagnosis and treatment are quite important.…”
Section: Introductionmentioning
confidence: 99%